Industrial training report: Pejabat Daerah Johor Bahru - Mohd Tahir, Ahmad Rabbanie Haqimy (Faculty of Business and Management, 2025)
Every full-time degree student who studies in Human Resources in UiTM Melaka Cawangan Bandaraya Melaka will undergo internship for six months or 24 weeks in order to complete their studies. I have been given an opportunity to join the Pejabat Daerah Johor Bahru to undergoing my internship. In Pejabat Daerah Johor Bahru, I have the opportunity to learn under five units which are Unit Keraian, Unit Pembangunan Masyarakat, Unit Pembangunan Fizikal, Unit Khas Perlesenan, and Unit Pentadbiran Dan Kewangan. For every month, I will rotate between these units to learn under them. Pejabat Daerah Johor Bahru let me experience to handle the engagement with the local community, the enforcement of special licenses which are entertainment and liquor license, event permit, local development and public welfare. For every company and government agencies, there will have their own strengths and weaknesses that we can identify throughout the internship. There will also opportunities and threats that we can learn to improve the current condition and the environment of the company or agency. Overall, my internship at Pejabat Daerah Johor Bahru provides me with valuable hands-on experience and allowing me to gain insights into the working of local government agency.